REASONS THAT LEAD PARENTS TO ENTER THEIR CHILDREN INCREASINGLY EARLY IN THE PRACTICE OF JUDO (Fiep Bulletin - online, 2013)
Judo is a sport that was developed through years of study with the objective of training the individual. Having a significant increase in the number of participants, we observed changes in the ways of dealing with practitioners through playfulness, like the color of the belt and judogis (kimono). From this background it became necessary to understand the reasons why parents would enroll their children at an earlier age in the sport of judo.  Qualitative and descriptive research was conducted by associations affiliated to Judo Team Ruffoni with 77 volunteer parents of judo students within the ages of 4 and 8 years old. According to the results, it can be noted that some questions were easy to understand, like the one that the parents are concerned about the motor skill development of their children, that is why they enroll them in Judo.  With all the gathered information we have concluded the need for further research to better understand and serve the practitioner of the sport.
Keywords: Judo; motivation; satisfaction.